Evaluasi Pelaksanaan Program Sekolah Penggerak di SMA Xaverius Ambon - Ufie, Alberto Boudewijn; Ratumanan, T.G.; Rumfot, Sumarni (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Sekolah Penggerak program has been implemented in several schools in Ambon, and in its implementation, several obstacles were encountered, namely the lack of infrastructure as a program requirement, and the presence of teaching staff who have not implemented the provisions of this program, inadequate learning implementation, to the implementation of evaluations that have an impact on the achievement of results. This research is an evaluative study, with the aim of describing the implementation of the Sekolah Penggerak Program, reviewed from the context component, input component, process component, product component, and what factors support and hinder its implementation, especially at SMA Xaverius Ambon. The evaluation model used is the CIPP model through a mixed methods approach. Quantitative analysis using questionnaire data interpreted statistically descriptively in four categories, namely very good, good, sufficient, less combined with qualitative data from interviews, documentation, and observations.